Model Pembelajaran PANORAMA Sebagai Upaya Penguatan Aktivitas, Berpikir Kritis dan Kerja Sama IPAS Kelas IV - zahratun nisa; Ahmad Suriansyah; Ratna Purwanti (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The implementation of Natural and Social Sciences (IPAS) subject within the context of Kurikulum Merdeka encounters several obstacles in developing 21st-century competencies. Problem identification results at SDN Pemurus Baru 2 Banjarmasin indicate minimal active student participation during the learning process, weak analytical thinking and problem-solving abilities, and ineffective teamwork and collaboration activities. This situation is further exacerbated by the limited creativity of educators in implementing innovative learning model and media variations. The purpose of this research is to optimize learning participation, critical thinking skills, and cooperative attitudes of fourth-grade students in IPAS subject with a focus on "Stories About My Region" material through the implementation of the PANORAMA learning model at SDN Pemurus Baru 2 Banjarmasin. The PANORAMA model is a synthesis of four learning approaches including Problem Based Learning, Number Head Together, SAVI (Somatic, Auditory, Visualization and Intellectually), and Make a Match that is constructed to facilitate students in exploring knowledge independently with a comprehensive perspective. The research approach applied is classroom action research (CAR) implemented at SDN Pemurus Baru 2 Banjarmasin with fourth-grade students as research subjects. This research design is focused on evaluating the progress of student learning participation, critical thinking abilities, and cooperative attitudes through the implementation of the PANORAMA learning model in the context of IPAS learning. Based on the problem identification that has been outlined, this research is projected to generate substantial improvements in student learning participation, development of critical thinking abilities that encompass competencies in asking appropriate questions, analyzing arguments, and overcoming problems, as well as strengthening cooperative attitudes that include interpersonal communication, leadership spirit, and group problem resolution. The PANORAMA model is expected to serve as an alternative solution in addressing IPAS learning problems in the Kurikulum Merdeka era and contribute to the formation of Pancasila student profiles that align with 21st-century needs